Analysis of Factors Related To Waiting Time For Services In The Outpatient Department of Manado Regional Hospital - Praiselia Angelina Lontaan; Fredrik G.Langi; John S. Kekenusa (CV. Inara, 2025)
Waiting time is a key indicator of healthcare service quality, particularly in outpatient care. Excessive waiting periods often lead to dissatisfaction, decreased trust in health systems, and can compromise care outcomes. In Indonesia, limited research has examined outpatient waiting times using multidimensional approaches that include both patient characteristics and perceptions. This study aimed to identify the factors associated with outpatient waiting times at Manado Regional General Hospital, with specific focus on demographic variables, timing of visits, and patient perceptions of service quality. A cross-sectional analytical study was conducted involving 154 outpatient respondents. Data were collected through structured questionnaires measuring demographics, visit timing, and 18 perception items which were reduced to latent constructs using exploratory factor analysis. Waiting time was categorized into <60 minutes and ≥60 minutes, in accordance with the Ministry of Health's Minimum Service Standards. Bivariate and multivariate logistic regression analyses were used to determine significant predictors of longer waiting times. More than half of the respondents (55%) reported waiting ≥60 minutes for outpatient services. Multivariate analysis revealed that male gender (aOR = 0.34; p = 0.015), having more than five previous visits (aOR = 0.06; p < 0.001), and higher perception scores regarding facilities and physician punctuality (aOR = 0.70; p = 0.004) were significantly associated with lower likelihood of long waiting times. Outpatient waiting times at Manado Regional Hospital are influenced by both patient-related and perceptual factors. Regular visitors and patients with more positive perceptions of service environment and physician punctuality experienced significantly shorter waiting times. Improving the physical environment of outpatient areas, ensuring physician punctuality, and supporting first-time patients may help reduce delays and improve service satisfaction.